2019
DOI: 10.3390/v11050397
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq Analysis Reveals Virus Diversity within Hawaiian Apiary Insect Communities

Abstract: Deformed wing virus (DWV) is the most abundant viral pathogen of honey bees and has been associated with large-scale colony losses. DWV and other bee-associated RNA viruses are generalists capable of infecting diverse hosts. Here, we used RNAseq analysis to test the hypothesis that due to the frequency of interactions, a range of apiary pest species would become infected with DWV and/or other honey bee-associated viruses. We confirmed that DWV-A was the most prevalent virus in the apiary, with genetically simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
1
37
1
Order By: Relevance
“…A potential absence of recombinants from other insects may be a result of the benefits or detriments of recombinant forms being specific to the honey bee host. The data in the present study differ to our previous findings [17], where we saw a number of non-honey bee samples containing high DWV levels and recombinants. We suggest this may be a result of different collection methodologies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A potential absence of recombinants from other insects may be a result of the benefits or detriments of recombinant forms being specific to the honey bee host. The data in the present study differ to our previous findings [17], where we saw a number of non-honey bee samples containing high DWV levels and recombinants. We suggest this may be a result of different collection methodologies.…”
Section: Discussioncontrasting
confidence: 99%
“…and a solitary bee Ceratina smaragdula increases compared to islands without Varroa, mirroring the situation in the honey bees [14]. Additionally, Brettell et al [17] showed that DWV was frequently detected in pest species that share the same space as honey bees, such as social wasps, hive beetles and ants, but variations in genetic variants between the bees and pest species existed, indicating that the situation was more complex than a simple spillover event. Loope at al.…”
Section: Introductionmentioning
confidence: 94%
“…In case of the more recently discovered viruses, such as MKV and LhuBLV1, the knowledge of disease symptoms, dynamics, or host range is very limited [36,37]. Studies suggest that the predatory wasp V. pensylvanica may represent an MKV reservoir on Hawaii [16,36]. We confirmed active MKV replication in three different wasp species and an overall high prevalence in Vespinae, supporting the potential virus reservoir.…”
Section: Host Range Of Rna Virusessupporting
confidence: 68%
“…Increasing evidence suggests that many of these pathogens are not specific to honey bees and instead are shared between many pollinator species and associated arthropods, including bumble bees and other wild bees [10][11][12]; bee predators, such as wasps [10,11]; and scavenging insects, such as ants, cockroaches, and beetles [10,[13][14][15]. Many of these host species have been found cohabiting in bee hives [13,15,16] or share floral resources with honey bees [17][18][19][20]. Although arthropods harbour an enormous diversity of viruses [21,22], little is known about the host range and dynamics of viruses within pollinator communities.…”
Section: Introductionmentioning
confidence: 99%
“…Three DWV genotypes have been described: DWV-A, DWV-B, and DWV-C (Mordecai et al, 2016b); only DWV-A (formally DWV) and DWV-B [formally V. destructor virus 1 or VDV-1 (Ongus et al, 2004)] are currently recognized by the International Committee on Taxonomy of Viruses. For clarity, we have employed the types A and B nomenclature widely adopted in recent publications (Martin et al, 2012;McMahon et al, 2016;Mordecai et al, 2016a,b;Brettell and Martin, 2017;Kevill et al, 2017;Gisder et al, 2018;Brettell et al, 2019;Dubois et al, 2019;Kevill et al, 2019;Remnant et al, 2019;Tehel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%